Development of Short-Form Versions of the Screener and Opioid Assessment for Patients with Pain-Revised (SOAPP-R): A Proof-of-Principle Study. Issue 7 (7th September 2016) - Finkelman, Matthew D.; Smits, Niels; Kulich, Ronald J.; Zacharoff, Kevin L.; Magnuson, Britta E.; Chang, Hong; Dong, Jinghui; Butler, Stephen F.
Abstract: Background. The Screener and Opioid Assessment for Patients with Pain–Revised (SOAPP-R) is a 24-item questionnaire designed to assess risk of aberrant medication-related behaviors in chronic pain patients. The introduction of short forms of the SOAPP-R may save time and increase utilization by practitioners. Objective. To develop and evaluate candidate SOAPP-R short forms. Design. Retrospective study. Setting. Pain centers. Subjects. Four hundred and twenty-eight patients with chronic noncancer pain. Methods. Subjects had previously been administered the full-length version of the SOAPP-R and been categorized as positive or negative for aberrant medication-related behaviors via the Aberrant Drug Behavior Index (ADBI). Short forms of the SOAPP-R were developed using lasso logistic regression. Sensitivity, specificity, and area under the curve (AUC) of all forms were calculated with respect to the ADBI using the complete data set, training-test analysis, and 10-fold cross-validation. The coefficient alpha of each form was also calculated. An external set of 12 pain practitioners reviewed the forms for content. Results. In the complete data set analysis, a form of 12 items exhibited sensitivity, specificity, and AUC greater than or equal to those of the full-length SOAPP-R (which were 0.74, 0.67, and 0.76, respectively). The short form had a coefficient alpha of 0.76. In the training-test analysis and 10-fold cross-validation, it exhibited an AUC value within 0.01 of that of the full-length SOAPP-R. The majority of external practitioners reported a preference for this short form. Conclusions. The 12-item version of the SOAPP-R has potential as a short risk screener and should be tested prospectively.